Altered expression of miR-21, miR-31, miR-143 and miR-145 is related to clinicopathologic features of colorectal cancer - Slabý, Ondřej; Svoboda, Marek; Fabian, Pavel; Šmerdová, Tamara; Knoflíčková, Dana; Bednaříková, Markéta; Nenutil, Rudolf; Vyzula, Rostislav (Oncology, 2007)
OBJECTIVES: Development and metastases of colorectal cancer (CRC) are characterized by multiple genetic alterations. MicroRNAs (miRNAs) are endogenously expressed regulatory noncoding RNAs. Previous, mainly preclinical studies showed altered expression levels of several miRNAs in CRC. METHODS: In our study, the expression levels of miR-21, miR-31, miR-143 and miR-145 in 29 primary colorectal carcinomas and 6 non-tumor adjacent tissue specimens were examined by real-time polymerase chain reaction. miRNA expression levels were also correlated with commonly used clinicopath-ologic features of CRC. RESULTS: Expression levels of analyzed miRNAs significantly differed among tumors and adjacent non-tumor tissues: miR-21 (p = 0.0001) and miR-31 (p = 0.0006) were upregulated, and miR-143 (p = 0.011) and miR-145 (p = 0.003) were downregulated in tumors. For the first time, a high expression of miR-21 was associated with lymph node positivity (p = 0.025) and the development of distant metastases (p = 0.009) in CRC patients. Thus, expression of miR-21 correlated with CRC clinical stage (p = 0.032). Furthermore, tumors >50 mm in maximal tumor diameter were characterized by lower expression of miR-143 (p = 0.006) and miR-145 (p = 0.003). We found no correlation between analyzed miRNAs and serum levels of carcinoembryonic antigen. CONCLUSION: Our results suggest possible roles of miR-21, miR-31, miR-143 and miR-145 in CRC. (c) 2008 S. Karger AG, Basel
Keywords: ženské pohlaví; Female; lidé středního věku; Humans; lidé; Aged; mikro RNA; financování organizované; Middle Aged; Clinical Trials as Topic; kolorektální nádory; Colorectal Neoplasms; senioři; Male; mužské pohlaví; klinické zkoušky jako téma; Financing, Organized; MicroRNAs